2005
DOI: 10.4049/jimmunol.175.9.6032
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Maturation, but Not CD8+ T Cell Induction, Is Dependent on Type I IFN Signaling during Vaccination with Adenovirus Vectors

Abstract: To understand how vaccines initiate adaptive immune responses, it is necessary to study how they interact with APCs such as dendritic cells (DCs). In this study, we analyzed interactions between recombinant adenovirus (Ad) vectors and mouse DCs. Mouse bone marrow-derived DCs transduced with Ad vectors produced type I IFN, which promoted the maturation of both transduced and bystander DCs. DCs transduced with a vector derived from a chimpanzee Ad serotype (AdC68) produced more type I IFN and matured more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…1B) increased over time and peaked at 12 h after infection. Consistent with the previous observations (19,20), these results indicate that type I IFNs can be induced rapidly upon adenoviral infection in vivo.…”
Section: Induction Of Type I Ifns Upon Adenoviral Infection In Vivosupporting
confidence: 81%
“…1B) increased over time and peaked at 12 h after infection. Consistent with the previous observations (19,20), these results indicate that type I IFNs can be induced rapidly upon adenoviral infection in vivo.…”
Section: Induction Of Type I Ifns Upon Adenoviral Infection In Vivosupporting
confidence: 81%
“…38 For example, chimpanzee-derived Ads have been shown to induce greater levels of type I IFNs than do HAd5 vectors both in vitro and in vivo. 72,73 This may partially explain the increased immune response to SAd23 observed in this study. Importantly both HAd3 and SAd23 specifically activated the alternative complement pathway in human serum, and the induction of IL-1a, MCP-1 and MIP-1b, and IL-10 were in part complement dependent in our mouse model.…”
Section: Had3 and Sad23 Activate Complement In Human Serummentioning
confidence: 66%
“…Another possible mechanism which could result in an abrogation of the proinflammatory cytokine response to FPV was a defect in the maturation in IFNAR Ϫ/Ϫ DCs. Previous studies with viruses including human adenovirus (AdV) have shown that DCs from IFNAR Ϫ/Ϫ mice are incapable of undergoing full maturation in response to viral infection (22,47) although other studies indicate little or no defect in DC maturation (33). The results of our experiments showed no obvious defect in the maturation of DCs from IFNAR Ϫ/Ϫ mice in response to FPV as upregulation of CD40, CD80, and CD86 was similar to that observed in the control groups, and the profiles were also broadly the same as those seen following stimulation with the synthetic TLR9 agonist, CpG.…”
Section: Discussionmentioning
confidence: 99%